(untitled) (Tzintzun, Revista de Estudios Históricos, 2021)
The present article analyzes the debates of Michoacánâ€™s Sixth Congress on the transition of the government system toward centralism demanded from several municipalities and towns in the state. The consulted documents show that arguments on the matter took place amidst the division of the legislature itself and under the pressure coming from several town halls and the armed forces that were seeking the AssemblyÂ´s pronouncement on favor of adopting centralism.